Biohydrogen Production from Organic Waste by Fermentation : A Review - Ainin Ainiyah; Rio Maulana Putra Istiawan; Mohammad Norazmi Ahmad; Ardika Nurmawati (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2026)
Biohydrogen production from organic waste represents a promising renewable energy alternative that can contribute to reducing dependence on fossil fuels. Biohydrogen is an environmentally friendly energy carrier, as it produces no carbon emissions during utilization and possesses a high energy content. Fermentation-based processes have been extensively studied due to their ability to operate without light, under relatively mild temperature and pressure conditions, and to utilize a wide variety of organic wastes as substrates. The present review article deals with the production of biohydrogen from organic waste by different fermentation methods, emphasizing the characteristics of the feedstock and the effect of the operating parameters on the efficiency of the process. The literature review demonstrated that dark fermentation is a promising sustainable route for biohydrogen production. But the relatively low hydrogen yields and the need for strict operating conditions mean that further optimization is needed to apply this technology effectively on an industrial scale, particularly in terms of improving the yield efficiency and reducing operational expenses. This study seeks to identify and compare the operating conditions reported in the literature that correlate with higher biohydrogen yield.